Analysis Of The Effectiveness Of Law Enforcement In The Framework Of Improving Taxpayer Compliance At Jakarta Kelapa Gading Service Office - Nurjanah, Sherly; Rulandari, Novianita; Abubakar, Ibrahim (Yayasan Sinergi Kawula Muda, 2023)
The purpose of this study is to determine the effectiveness of law enforcement in order to increase taxpayer compliance at the Jakarta Kelapa Gading service office. Tax law enforcement is carried out by way of supervision, tax audit, tax investigation, and tax collection. This study uses a qualitative method with a descriptive approach. Based on the results of this study, there are still taxpayers who have not carried out their obligations in reporting SPT and paying their taxes, so that taxpayers are still subject to administrative sanctions.